Effects of Computer Animation on Elementary Students' Understanding of Physical State Changes - Nuraini Nuraini; Masfufah Masfufah (Journal of Innovation and Research in Primary Education, 2026)
Computer animation has emerged as a promising educational tool, yet its effectiveness in resource-constrained Indonesian elementary schools remains underexplored, particularly for teaching abstract scientific concepts. This study examined whether computer animation learning media significantly affects third-grade students' learning outcomes in understanding changes in object forms. A quasi-experimental design with nonequivalent control groups was employed, involving 30 third-grade students at SDN 12 Palu, Indonesia. The experimental group (n=15) received animation-based instruction via Google Meet, while the control group (n=15) received conventional image-based instruction via WhatsApp. A validated 15-item achievement test (α=0.87) was administered as pretest and posttest. Data were analyzed using independent samples t-test. Although the experimental group achieved higher posttest scores (M=86.67, SD=11.75) compared to the control group (M=72.67, SD=17.92), the difference was not statistically significant (t(28)=2.53, p=0.17). Both groups demonstrated improved learning outcomes, with mean gains of 28.67 and 10.00 points respectively. The null findings suggest that animation's theoretical advantages did not materialize under pandemic-constrained online delivery conditions. Implementation quality, technological infrastructure limitations, and online delivery mediation likely offset potential cognitive benefits. Results underscore the importance of optimal implementation conditions for educational technology effectiveness in developing country contexts.